A cohort study of microwave ablation and surgery for low-risk papillary thyroid microcarcinoma - Yuan Zu (Taylor & Francis Group, 2021)
Background The optimal treatment method for papillary thyroid microcarcinoma (PTMC) is lacking consensus. Here we aimed to compare the efficacy and safety of surgery and microwave ablation (MWA) for PTMC. Methods The clinical data of 644 patients with PTMC treated between July 2013 and June 2020 were retrospectively analyzed. A total of 320 and 324 patients underwent MWA and surgery, respectively. We observed lesion changes in the MWA group and compared the recurrence, metastasis, complications, and other health economic indicators between the 2 groups. Results The mean follow-up time was 890.7 ± 532.9 (187.9–2679.0) days in the MWA group and 910.9 ± 568.4 (193.8–2821.5) days in the surgery group. In the MWA group, lesion volume increased significantly after ablation and then gradually decreased. The final lesion volume reduction rate was 90.73% ± 7.94%, and 193 lesions (60.3%) disappeared completely. There were no significant intergroup differences in recurrence or metastasis. The incidence of main complications (temporary hypothyroidism, hypoparathyroidism, and temporary hoarseness) was significantly lower in the MWA group than in the surgery group (p < 0.001). The treatment time, intraoperative blood loss, and hospital stay were significantly lower in the MWA group than in the surgery group (p < 0.001). Conclusions MWA is effective for treating PTMC, with a low incidence of complications and less trauma. The rates of post-treatment recurrence and metastasis are similar to those of surgery, indicating that MWA is a suitable alternative to surgery.